Determination of the small-strain stiffness of hard soils by means of bender elements and accelerometers - Ferreira, Cristiana (2014)
Direct determination of seismic wave velocities in the laboratory is becoming common practice worldwide, given its great potential in the definition of the stiffness at very small strains. One of the techniques for seismic wave measurement makes use of piezoelectric transducers, such as bender elements (BEs). However, some limitations remain to the applicability of this technique, namely for stiff geomaterials, such as compacted soils, naturally or artificially cemented soils and soft or weak rocks. For this purpose, two accelerometers have been used in conjunction with BEs. In the present paper, this combined test setup implemented on a stress-path triaxial chamber will be detailed. An application study will be presented for a hard soil, prepared by laboratory compaction and tested in triaxial compression at different isotropic stress levels. The equipments, procedures and interpretation analyses will also be described. The advantages of this setup are twofold: i) the interpretation of the acceleration measurements is straightforward, since the signals are of the same nature; ii) these measurements can be used to verify the bender element signals, and thus minimize the subjectivity of the interpretation of BE results. Additionally, the accelerometers can be used autonomously wherever the interpretation of BEs becomes too complex. The results of this research enabled to validate the interpretation methods used for bender element testing. Moreover, this combined setup of transducers provided a simple yet powerful tool for eliminating the subjectivity inherent to BE testing, enabling reliable measurements of small-strain stiffness for a wide range of materials.